Challenges and solutions for long-term permafrost borehole temperature monitoring and data interpretation - R. Luethi; M. Phillips (Geographica Helvetica, 2016)
Long-term borehole temperature monitoring in mountain permafrost environments is challenging under the hostile conditions reigning in alpine environments. On the basis of data measured in the SLF borehole network we show three situations where ground temperature data should be interpreted with caution. (i) Thermistors have the tendency to drift, particularly if exposed to moisture or mechanical strain. This induces apparent warming or cooling, which can be difficult to differentiate from real ground temperature changes. Recalibration of thermistor chains is impossible if they cannot be extracted as a result of borehole deformation in creeping permafrost terrain. A solution using zero-curtain-based detection of drift and correction of data is presented. This method is however limited to the active layer, due to the lack of a reference temperature at greater depth. (ii) In contrast to drift-induced apparent warming, actual warming may be induced by natural processes or by the effects of construction activity. (iii) Control data from neighbouring boreholes are sometimes used to fill data gaps and discern drift – however these data may only underline the strong spatial variability of ground temperatures rather than provide measurement redundancy. A selection of recently observed problems regarding borehole monitoring in a hostile measurement environment are discussed, and advantages and possible drawbacks of various solutions including measurement redundancy or alternate instrumentation are presented.